The politics of union-government relations: Public transport in two Australian states. (1st October 2008) - ,; ,
Abstract : Successive governments, particularly in the Anglo-American world, have sought to redefine the state by redrawing the boundaries between the public and private sectors, with marked implications for trade unions. One consequence of this process is that relations between unions and governments are reforged. In Australia, governments have initiated comprehensive processes of corporatisation and privatisation. One result is that previously close and often informal partnership arrangements (in the case of Labor governments) have changed. This type of institutional reorganisation prompts a reassessment of union-government relations as well as a complex working out of new modes of governance. This article explores these themes in relation to public transport in two Australian states: New South Wales and Victoria.